Відповідь: a - перший катет, b - другий катет, с - гіпотенуза.
Нехай другий катет = с-2, тоді
c^2 = a^2 + b^2
c^2 = 6^2 + (c-2)^2
c^2 = 36 + c^2 - 4c + 4
4c = 40
c = 10
Гіпотенуза = 10, перший катет - 6, другий катет - (10-2) = 8
P = 10+6+8 = 24 (см)
Відповідь: a - перший катет, b - другий катет, с - гіпотенуза.
Нехай другий катет = с-2, тоді
c^2 = a^2 + b^2
c^2 = 6^2 + (c-2)^2
c^2 = 36 + c^2 - 4c + 4
4c = 40
c = 10
Гіпотенуза = 10, перший катет - 6, другий катет - (10-2) = 8
P = 10+6+8 = 24 (см)